The Impact Of Communication On Project Performance In Construction Projects - Satoinong, Laif; Desnalia, Desnalia; Mintura, Steven; Paroipo, Wahyu Trifadil; Gulthom, Abel; Simamora, Jawarta; Zebua, Dermawan (Innovative Research in Civil and Environmental Engineering, 2024)
Effective communication is a critical factor influencing the success of construction projects, impacting project performance in terms of time, cost, and quality. This study investigates the relationship between communication practices and project outcomes in the construction industry. Utilizing a mixed-methods approach, quantitative data were collected through surveys with project stakeholders, while qualitative insights were obtained from interviews with experienced construction professionals. Results indicate that projects with structured and clear communication practices demonstrate improved performance, reduced delays, and cost efficiency. Key barriers identified include language differences, inconsistent information flow, and delayed updates. The study highlights the importance of adopting digital communication tools and standardized protocols to enhance communication effectiveness. These findings underscore the need for strategic communication management to achieve optimal project performance